Adult onset familiar dystonia-plus syndrome: A novel presentation of IRF2BPL-associated neurodegeneration. (January 2022) - Antonelli, Francesca; Grieco, Gaetano; Cavallieri, Francesco; Casella, Antonella; Valente, Enza Maria
Abstract: Pathogenic variants of the IRF2BPL gene have been mostly associated with early onset epileptic encephalopathy. Movement disorders such as dystonia and ataxia were also reported, with symptoms mainly developing between childhood and adolescence. Here we describe a family with several members affected by a late onset dystonic and ataxic progressive syndrome, caused by a novel heterozygous pathogenic variant in the IRF2BPL gene. Highlights: IRF2BPL heterozygous variants have been associated with a range of neurological syndromes. Childhood-onset epileptic encephalopathy is the most documented phenotype. We report a family with IRF2BPL-related late onset dystonic and ataxic syndrome. IRF2BPL gene should be included in gene panels for ataxic and dystonic syndromes.